2022
DOI: 10.1590/1980-5373-mr-2021-0125
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and Economic Evaluation of the Cocoa Bean Shell as a Corrosion Inhibitor in Acidic Medium

Abstract: The inhibition effect of the cocoa bean shell powder (CBSP) on SAE 1008 carbon steel was studied in acidic medium (HCl 0.5 mol L -1 ) by electrochemical techniques and gravimetric measurements. Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscopy (SEM) were used to the chemical and morphological characterization. The gravimetric and EIS results showed that the corrosion rate decreases with increasing inhibitor concentration, reaching the maximum value of 97.92% in 1.77 g L -1 inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The direct cost of producing 1,000 g of the corrosion inhibitor under study in a laboratory setting was assessed. As a result, the energy costs associated with milling, drying, and screening as well as the transportation costs of the residue removal at the facility was taken into account ( Carvalho et al, 2022 ), $ 0.09 was used. The average market value of commercial inhibitors was given in the work of ( Carvalho et al, 2022 ) and these data are displayed in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The direct cost of producing 1,000 g of the corrosion inhibitor under study in a laboratory setting was assessed. As a result, the energy costs associated with milling, drying, and screening as well as the transportation costs of the residue removal at the facility was taken into account ( Carvalho et al, 2022 ), $ 0.09 was used. The average market value of commercial inhibitors was given in the work of ( Carvalho et al, 2022 ) and these data are displayed in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The methodology used is the standard used in the area of corrosion of materials. Some authors who studied some residues as a natural corrosion inhibitor used this same methodology, such as Santos et al (2021) in their study on Palmiste pie powder as a natural corrosion inhibitor; and Carvalho et al (2022) in their study of cocoa bean husk as a natural corrosion inhibitor. For a better understanding of the research, the experimental part is divided into preparation of the residue that will be tested as an inhibitor, preparation of the metal that will be used as a substrate, the characteristic tests of the corrosion area (electrochemical and gravimetric) and finally a characterization through Scanning Electron Microscopy and Energy Dispersive X-Ray Spectroscopy.…”
Section: Methodsmentioning
confidence: 99%
“…Shalabi and Nazeer (2015) in the evaluation of the extract of different parts of the species Schinus terebinthifolius cultivated in Egypt as an inhibitor of corrosion of carbon steel, indicated a mixed performance of the mentioned inhibitor. Carvalho et al (2022) detected mixed behavior in their evaluation of cocoa bean husk powder as an inhibitor of corrosion of carbon steel in acidic medium. Source: Authors.…”
Section: Potentiodynamic Polarization Curvesmentioning
confidence: 99%
“…In addition, the authors reported that for all of the concentrations tested, CBS powder did not show efficient corrosion, while hydroalcoholic extract presented a good performance at the lowest concentration (0.4 g/L). The same authors [136] evaluated the corrosion-inhibitory properties of CBS powder with the same steel but, in this case, in an acidic medium (HCl 0.5 mol/L). An excellent corrosion inhibition efficiency (96%) was achieved at the lowest concentration of inhibitor tested (0.4 g/L), revealing the potential of CBS as an efficient corrosion inhibitor for carbon steel.…”
Section: Corrosion Inhibitormentioning
confidence: 99%